Advances in the immunological microenvironment and immunotherapy of bladder cancer - Meng, Le; Zhu, Xiangyu; Ji, Xuran; Wang, Bowen; Zhang, Haoxun; Zhang, Guoling; Xue, Yue; Wang, Chunyang (Frontiers in Immunology, 2025)
Bladder cancer remains a significant global health challenge, particularly affecting male populations. While radical cystectomy and chemotherapy have been mainstays of treatment, their substantial morbidity and impact on quality of life have driven the development of bladder-preserving immunotherapeutic strategies. Clinical trial data support the use of ICIs as first-line therapy for cisplatin-ineligible patients, second-line treatment for platinum-refractory disease, and maintenance therapy. This review comprehensively summarizes the advances in bladder cancer immunotherapy, focusing on the tumor immune microenvironment and emerging treatment modalities, as well as the roles of immune checkpoint inhibitors (ICIs) targeting PD-1/PD-L1 and CTLA-4 pathways, which have demonstrated remarkable efficacy in both muscle-invasive (MIBC) and non-muscle invasive bladder cancer (NMIBC). This review also provides novel approaches including combination immunotherapies, tumor vaccines, adoptive cellular therapies, and oncolytic viruses. Overall, these immunotherapeutic advances are transforming bladder cancer management, offering improved outcomes while reducing treatment morbidity.